'Being a presence': The ways in which family support workers encompass, embrace, befriend, accompany and endure with families of life-limited children. (September 2015) - Carter, Bernie; Edwards, Maria; Hunt, Anne
Children with life-limiting and disabling conditions are surviving longer than previously, and many require palliative and supportive care, usually at home. Home-based care can put family life under considerable strain, as parents care for their child's complex, often unpredictable, continuing care needs. Rainbow Trust Children's Charity aims to bridge gaps in services for children with life-threatening or terminal conditions by providing family support workers (FSWs). The study used a range of methods (surveys, interviews and ethnographic observation) approach to explore key aspects of the work of the FSWs. The target population for the surveys was families with a child having complex, life-threatening or terminal conditions receiving care from FSWs. The participants included 55 families (12 bereaved) and 39 children aged 2–18 years. Thematic analysis revealed how the FSWs became a presence in families' lives in three main ways: (1) encompassing and embracing families through supporting needs and promoting resilience; (2) befriending and bonding through developing knowledge, trusting relationships and a sense of closeness; and (3) accompanying and enduring by 'being with' families in different settings, situations and crises and by enduring alongside the families. The study demonstrated the fundamental importance of workers who are able to provide aspects of support that is usually not provided by other services.